Comparative Planning of Flattening-Filter-Free and Flat Beam IMRT for Hypopharynx Cancer as a Function of Beam and Segment Number - Dzierma, Yvonne (Public Library of Science, 2014)
Although highly conformal dose distributions can be achieved by IMRT planning, this often requires a large number of segments or beams, resulting in increased treatment times. While flattening-filter-free beams offer a higher dose rate, even more segments may be required to create homogeneous target coverage. Therefore, it is worthwhile to systematically investigate the dependence of plan quality on gantry angles and number of segments for flat vs. FFF beams in IMRT planning. For the practical example of hypopharynx cancer, we present a planning study of flat vs. FFF beams using three different configurations of gantry angles and different segment numbers. The two beams are very similar in physical properties, and are hence well-suited for comparative planning. Starting with a set of plans of equal quality for flat and FFF beams, we assess how far the number of segments can be reduced before the plan quality is markedly compromised, and compare monitor units and treatment times for the resulting plans. As long as a sufficiently large number of segments is permitted, all planning scenarios give good results, independently of gantry angles and flat or FFF beams. For smaller numbers of segments, plan quality decreases both for flat and FFF energies; this effect is stronger for fewer gantry angles and for FFF beams. For low segment numbers, FFF plans are generally worse than the corresponding flat beam plans, but they are less sensitive to a decrease in segment number if many gantry angles are used (18 beams); in this case the quality of flat and FFF plans remains comparable even for few segments.